Congenital syphilis in Mexico. Analysis of national and international standards from the perspective of laboratory diagnosis - Herrera-Ortiz, Antonia; López-Gatell, Hugo; García-Cisneros, Santa; Cortés-Ortiz, María Alejandra; Olamendi-Portugal, María; Hegewisch-Taylor, Jennifer; Sánchez-Alemán, Miguel Ángel (Gaceta médica de México, 2019)
Congenital syphilis continues to be a public health problem in Mexico. To assess the similarities and differences between national standards, guidelines and international documents related to the detection of syphilis in pregnant women and congenital syphilis. Two algorithms were developed based on the standard of female care during pregnancy and on the standard for prevention and control of sexually transmitted infections. Based on the Centers for Disease Control (CDC) guidelines, algorithms were developed for syphilis during pregnancy, syphilis in the newborn and sexual contacts. The standard for pregnancy mentions that syphilis testing should be carried out in every pregnant woman on her first contact or at delivery, without diagnostic tests being specified. The Official Mexican Standard (NOM) on sexually transmitted infections mentions the traditional algorithm for syphilis detection, treatment follow-up, coinfection with human immunodeficiency virus and congenital syphilis criteria. The CDC recommend reverse algorithm, antibody titer, treatment and follow-up as part of diagnosis. The elimination of mother-to-child transmission of syphilis requires NOMs updating and homogenizing, as well as the study of stillbirths and neonates born to mothers with syphilis.